Tryptophan metabolism as a common therapeutic target in cancer, neurodegeneration and beyond - Platten, Michael; Opitz, Christiane (Nature reviews. Drug discovery, 2019)
Imbalances in the kynurenine pathway (KP) of tryptophan metabolism are associated with CNS disorders, infectious diseases, autoimmune diseases and cancer, highlighting KP enzymes as potential therapeutic targets. Here, Platten and colleagues provide an overview of the physiological and pathophysiological roles of tryptophan metabolism, focusing on the clinical potential and challenges associated with targeting this pathway.